Single‐Molecule Counting of High‐Sensitivity Troponin I in Patients Referred for Diagnostic Angiography: Results From the CASABLANCA (Catheter Sampled Blood Archive in Cardiovascular Diseases) Study. Issue 6 (8th March 2018) - McCarthy, Cian P.; Ibrahim, Nasrien E.; Lyass, Asya; Li, Yiwei; Gaggin, Hanna K.; Simon, Mandy L.; Mukai, Renata; Gandhi, Parul; Kelly, Noreen; Motiwala, Shweta R.; van Kimmenade, Roland R. J.; Massaro, Joseph M.; et al.
Abstract : Background: The meaning of high‐sensitivity troponin I (hsTnI) concentrations in patients without acute myocardial infarction (MI) requires clarity. We hypothesized that among patients referred for diagnostic coronary angiography without acute MI, hsTnI concentrations would correlate with prevalent coronary artery disease (CAD) and predict incident cardiovascular events and mortality. Methods and Results: We measured hsTnI using a single‐molecule counting assay (99th percentile, 6 ng/L) in samples from 991 patients obtained at the time of angiography. Concentrations of hsTnI were assessed relative to the severity of CAD and prognosis during mean follow‐up of 3.7 years. Median hsTnI concentration was 4.19 ng/L; 38% of patients had hsTnI concentrations ≥99th percentile. Across increasing hsTnI quartiles, patients had higher prevalence of angiographic CAD; in multivariate models, hsTnI ≥99th percentile independently predicted obstructive CAD (odds ratio: 2.57; P <0.001) and incident MI (hazard ratio [HR]: 2.68; P <0.001), cardiovascular death (HR: 2.29; P =0.001), and all‐cause death (HR: 1.84; P =0.004). In those with >70% coronary stenosis, hsTnI ≥99th percentile independently predicted incident MI (HR: 1.87; P =0.01), cardiovascular mortality (HR: 2.74; P =0.001), and the composite end point of MI and all‐cause death (HR: 2.06; P <0.001). In participants with coronary stenosis <70%, hsTnI ≥99th percentile even more strongly predicted incident MI (HR: 8.41; P <0.001), cardiovascular mortality (HR: 3.60; P =0.03), and the composite end point of MI and all‐cause death (HR: 3.62; P <0.001). Conclusions: In a large prospective cohort of patients who were free of prevalent MI and undergoing diagnostic coronary angiography, hsTnI concentrations were associated with higher prevalence of CAD and predicted incident MI, cardiovascular death, and all‐cause death. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00842868.